Some economic objections against the custom of ?fortuning? daughters, that prevails amongst the farming classes in Munster - Preston, S. P. (Statistical and Social Inquiry Society of Ireland, 1879)
He who carefully studies the social condition of our agricultural population cannot fail to see many things capable of improvement, in which, if there is to be any improvement at all, it must be initiated within the social fabric?customs that ought to be honoured in the breach, not in the observance?habits and traditions that only handicap us as a people, and prejudice our chances of taking a place amongst progressive nations.
Read before the Society, 20 May1979
Keywords: Irish agriculture; Rural Ireland; Farmers' saving; Female inheritance; 314.15